Clay stabilizer as well as preparation method and application thereof

By preparing a clay stabilizer with small molecule multi-point adsorption, the problem of clay stabilizers being easily decomposed at high temperatures and clogging low-permeability rock layers in the existing technology has been solved, achieving the effect of effectively preventing clay migration and resisting expansion.

CN119119108AActive Publication Date: 2024-12-13CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310690517.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-13
Estimated Expiration
2043-06-12

AI Technical Summary

Technical Problem

Existing clay stabilizers are prone to decomposition at high temperatures, resulting in weak bonding between clay and rock strata. They cannot effectively prevent clay migration and easily clog the pores of low-permeability rock strata.

Method used

Clay stabilizers were prepared by amidation reaction of polymeric amines and aminosilanes with pyromellitic acid. By using graphite, tin chloride and bentonite in specific proportions as catalysts, clay stabilizers with small molecular size, multi-point adsorption and high temperature stability were formed.

Benefits of technology

It achieves good anti-swelling properties even at a high temperature of 350°C, prevents clay migration rate of up to 98%, and avoids clogging of low-permeability rock layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_8
    Figure SMS_8
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention provides a clay stabilizer and a preparation method thereof, and the clay stabilizer is prepared by taking polyethylene amine or polyether amine, amino silane and trimesic acid as raw materials, taking an aprotic high-polarity organic solvent as a solvent and taking solid acid as a catalyst through amidation reaction. The clay stabilizer provided by the invention has the advantages of small molecular weight, good anti-swelling effect, strong binding force with stratum, effective prevention of migration of clay particles, high temperature resistance and the like. The anti-swelling rate is greater than or equal to 85% under the dosage of 0.5%, the anti-swelling rate is greater than or equal to 85% after aging at 350 DEG C under the dosage of 1%, and the washable rate is greater than or equal to 98%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of oil production engineering, and in particular, relates to a clay stabilizer and a preparation method and application thereof. Background Art

[0002] Clay is a common mineral in formation rocks. Clay has the characteristic of swelling when it comes into contact with water. Therefore, during the process of reservoir development such as water injection, acidification or fracturing in oil fields, the voids in clay-rich reservoirs will be reduced due to clay swelling, and the pores will be blocked in large quantities, causing water-sensitive damage. In order to reduce this reservoir damage, clay anti-swelling agents are widely used. Clay anti-swelling agents can effectively adsorb on the surface of clay to prevent water-sensitive minerals in the reservoir from hydrating, swelling and dispersing and migrating, thereby damaging the oil and gas layers and affecting the effect of oil field development.

[0003] The commonly used anti-swelling agents include inorganic salts, cationic polymers and quaternary ammonium salts. Inorganic salts are the earliest used clay anti-swelling agents, mainly using inorganic salt ions such as K + Embedded in the clay crystal structure to neutralize the electronegativity of the clay, but inorganic salt clay anti-swelling agents have weak bonding with the formation and poor anti-clay migration ability. Cationic polymer molecules contain multiple positive charges and can be adsorbed at multiple points on the surface of clay minerals. They have good anti-swelling effects and are resistant to erosion, but they have large molecular weights and are easy to block the pore throats of formations, harming the permeability of formations, and are not suitable for dense formations. On the other hand, cationic polymers have poor temperature resistance and are prone to decomposition at high temperatures, which makes their anti-swelling effects disappear. Although quaternary ammonium salts have small molecular weights and will not clog the formations themselves, they can only produce single-point adsorption on the clay surface, so their anti-swelling effects are not as good as cationic polymers.

[0004] CN105198757B discloses a small cationic diquaternary ammonium salt clay stabilizer and a preparation method thereof. Epichlorohydrin, a small molecular tertiary amine and hydrochloric acid are used as raw materials to prepare a clay anti-swelling agent with a relatively high charge density. However, since the adsorption sites on the clay surface are still relatively small, the anti-swelling effect is still not ideal.

[0005] CN106279661B discloses a quaternary ammonium salt type cationic polymer, which is obtained by chemical reaction of aliphatic amine, acid, epichlorohydrin and terminal diamine. The polymer can be adsorbed on the surface of clay particles, which can greatly improve the anti-swelling effect of clay anti-swelling agent at low dosage. However, due to its excessively large molecular weight and poor temperature resistance, it cannot be applied to low permeability formations, limiting its application range.

[0006] CN101921366A discloses a three-branched cationic polymer synthesized from diallyl ammonium chloride and triallyl ammonium chloride, which is used to stabilize clay in the oil recovery process. However, studies have shown that high molecular weight cationic polymers are not suitable for low permeability formations, and are prone to form emboli in the pore channels of the formation, thereby blocking the formation; at the same time, due to the long molecular chain and the large number of cationic groups contained in the polymer, it is easy to react with a treatment agent containing anionic groups, which greatly affects the effect of the treatment agent.

[0007] Therefore, it is necessary to develop an efficient clay stabilizer with low molecular weight, multi-point adsorption, strong bonding with the formation, and good anti-swelling performance. Summary of the invention

[0008] The present invention aims at the technical problems existing in the background technology and provides a clay stabilizer and a preparation method thereof, so as to solve the problems that the existing clay stabilizers have low high temperature resistance, weak bonding with the formation, poor ability to prevent clay migration and blockage of low permeability formation pores; the clay stabilizer provided by the present invention has the advantages of small molecular weight, good anti-swelling effect, strong bonding with the formation, effective prevention of clay particle migration, high temperature resistance and the like.

[0009] The present invention achieves the above-mentioned purpose through the following technical solutions.

[0010] A clay stabilizer according to the present invention has a structure shown in formula (1) or formula (2);

[0011] Wherein, n1=0 or 1, n2=any integer from 0 to 4, n3=any number from 1 to 5, R1 and R2 are the same or different and are independently H, CH3, C2H 5、 .

[0012] Furthermore, the preparation method of a clay stabilizer described in the present invention uses polyethyleneamine or polyetheramine, aminosilane, and trimesic acid as raw materials, a non-protonic high-polarity organic solvent as solvent, and a solid acid as catalyst to obtain the clay stabilizer through an amidation reaction.

[0013] Furthermore, in the method for preparing a clay stabilizer described in the present invention, the conditions for the amidation reaction include: 均苯三酸 :n 多乙烯胺或聚醚胺 :n 胺基硅烷 =1:3:1.5~1:6:3, the amount of solid acid catalyst added is 0.5%-2% of the total mass of polyethyleneamine or polyetheramine, aminosilane and trimesic acid, the reaction temperature is 130-190℃, and the reaction time is 3-6h.

[0014] Furthermore, in the method for preparing a clay stabilizer described in the present invention, the polyethyleneamine is at least one of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and pentaethylenehexamine.

[0015] Furthermore, in the method for preparing a clay stabilizer described in the present invention, the aprotic high-polarity organic solvent is at least one of dimethyl sulfoxide and dimethylformamide.

[0016] Furthermore, in the method for preparing a clay stabilizer described in the present invention, the trimesic acid is at least one of trimesic acid and trimesic acid.

[0017] Furthermore, in the preparation method of a clay stabilizer described in the present invention, the aminosilane is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminopropyltrihydroxysilane.

[0018] The present invention also provides a method for preparing the clay stabilizer. The solid acid catalyst is prepared from graphite, tin chloride, bentonite, potassium permanganate and concentrated sulfuric acid.

[0019] Furthermore, in the preparation method of a clay stabilizer described in the present invention, the solid acid catalyst is composed of 10-30% graphite (400-600 mesh), 20-45% tin chloride and 25-70% bentonite by mass fraction, and is prepared by soaking, drying and calcining at 500-600°C in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:10-20.

[0020] The clay stabilizer of the present invention is applied in the field of oil production in oil fields.

[0021] The effective effects and features of the present invention are: (1) The clay stabilizer of the present invention contains amine groups in its molecular structure, which form amine positive ions in aqueous solution with high charge density. It can neutralize the negative charge on the surface of the clay and can also electrostatically adsorb to the formation, thus making it have excellent anti-swelling performance and water washing resistance. The anti-swelling rate reaches more than 85% at a dosage of 0.5%; (2) The clay stabilizer of the present invention contains a siloxane group in its molecular structure. The siloxane group uses the hydrolyzed Si-OH to undergo a polycondensation reaction with the Si-OH on the clay surface to achieve chemical adsorption of the clay stabilizer on the clay surface, thereby further enhancing the water washability of the clay stabilizer and the performance of preventing clay migration, and the water washability rate reaches more than 98%; (3) The clay stabilizer of the present invention contains a rigid group benzene ring in its molecular structure, and has good temperature resistance, which can reach a temperature of 350°C; (4) The clay stabilizer of the present invention has a small molecular weight and will not cause blockage in low permeability formations; (5) The solid acid catalyst developed by the present invention contains an acidic group and a hydrophilic group, which greatly improves the catalytic activity of the solid acid. Implementation

[0022] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described in combination with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments in the invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0023] A four-necked flask equipped with a stirring paddle, a thermometer, a constant pressure dropping funnel and a water separator was placed in an oil bath, 100 g of dimethyl sulfoxide, 70 g of trimesic acid, 7.02 g of a solid acid catalyst and 221 g of 3-aminopropyltriethoxysilane were added, the temperature was slowly raised to 130°C and the reaction was carried out for 1 h. 60 g of ethylenediamine was added through a constant pressure dropping funnel. After the addition was completed, the reaction was continued at 130°C for 2 h. Finally, the solvent dimethyl sulfoxide was removed by reduced pressure distillation to obtain clay stabilizer S1.

[0024] The solid acid catalyst is composed of 10% graphite (400 mesh), 20% tin chloride and 70% bentonite in a mass fraction, and is prepared by soaking, drying and calcining at 500° C. in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:10. Example 2

[0025] A four-necked flask equipped with a stirring paddle, a thermometer, a constant pressure dropping funnel and a water separator was placed in an oil bath, 100 g of dimethyl sulfoxide, 70 g of trimesic acid, 0.731 g of a solid acid catalyst and 89.5 g of 3-aminopropyltrimethoxysilane were added, the temperature was slowly raised to 130°C and the reaction was carried out for 1.5 h. 206 g of diethylenetriamine was added through a constant pressure dropping funnel. After the addition was completed, the reaction was continued at 190°C for 4.5 h. Finally, the solvent dimethyl sulfoxide was removed by reduced pressure distillation to obtain clay stabilizer S2.

[0026] The solid acid catalyst is composed of 20% graphite (500 mesh), 30% tin chloride and 50% bentonite in a mass fraction, and is prepared by soaking, drying and calcining at 550° C. in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:15. Example 3

[0027] A four-necked flask equipped with a stirring paddle, a thermometer, a constant pressure dropping funnel and a water separator was placed in an oil bath, 100 g of dimethyl sulfoxide, 70 g of trimesic acid, 3.65 g of a solid acid catalyst and 91 g of 3-aminopropyltrihydroxysilane were added, the temperature was slowly raised to 140°C and the reaction was carried out for 2 h. 195 g of triethylenetetramine was added through a constant pressure dropping funnel. After the addition was completed, the reaction was continued at 170°C for 3 h. Finally, the solvent dimethyl sulfoxide was removed by reduced pressure distillation to obtain clay stabilizer S3.

[0028] The solid acid catalyst is composed of 30% graphite (600 mesh), 20% tin chloride and 50% bentonite in a mass fraction, and is prepared by soaking, drying and calcining at 600°C in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:20. Example 4

[0029] A four-necked flask equipped with a stirring paddle, a thermometer, a constant pressure dropping funnel and a water separator was placed in an oil bath, 100 g of dimethylformamide, 84 g of trimesic acid, 5.82 g of a solid acid catalyst and 120 g of 3-aminopropyltriethoxysilane were added, the temperature was slowly raised to 130°C and the reaction was carried out for 2 h. 378 g of tetraethylenepentamine was added through a constant pressure dropping funnel. After the addition was completed, the reaction was continued at 160°C for 4 h. Finally, the solvent dimethyl sulfoxide was removed by reduced pressure distillation to obtain clay stabilizer S4.

[0030] The solid acid catalyst is composed of 15% by mass of graphite (450 mesh), 45% by mass of tin chloride and 40% by mass of bentonite, and is prepared by soaking, drying and calcining at 500° C. in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:20. Example 5

[0031] A four-necked flask equipped with a stirring paddle, a thermometer, a constant pressure dropping funnel and a water separator was placed in an oil bath, 100 g of dimethyl sulfoxide, 84 g of trimesic acid, 7.452 g of a solid acid catalyst and 179 g of 3-aminopropyltrimethoxysilane were added, the temperature was slowly raised to 140°C and the reaction was carried out for 1.5 h. 232 g of pentaethylenetetramine was added through a constant pressure dropping funnel. After the addition was completed, the reaction was continued at 180°C for 1.5 h. Finally, the solvent dimethyl sulfoxide was removed by reduced pressure distillation to obtain clay stabilizer S5.

[0032] The solid acid catalyst is composed of 20% graphite (500 mesh), 20% tin chloride and 60% bentonite in a mass fraction, and is prepared by soaking, drying and calcining at 600°C in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:10. Example 6

[0033] A four-necked flask equipped with a stirring paddle, a thermometer, a constant pressure dropping funnel and a water separator was placed in an oil bath, 100 g of dimethylformamide, 84 g of trimesic acid, 7.42 g of a solid acid catalyst and 137 g of 3-aminopropyltrihydroxysilane were added, the temperature was slowly raised to 130°C and the reaction was carried out for 2 h. 150 g of a polyetheramine having a structural formula as shown in Formula 1 was added through a constant pressure dropping funnel. After the addition was completed, the reaction was continued at 150°C for 3 h. Finally, the solvent dimethyl sulfoxide was removed by vacuum distillation to obtain a clay stabilizer S6.

[0034] The structural formula of polyetheramine is: Formula (3) The solid acid catalyst is composed of 30% graphite (400 mesh), 45% tin chloride and 25% bentonite in a mass fraction, and is prepared by soaking in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:15, drying, and calcining at 550°C.

[0035] Example 7 A four-necked flask equipped with a stirring paddle, a thermometer, a constant pressure dropping funnel and a water separator was placed in an oil bath, 100 g of dimethylformamide, 70 g of trimesic acid, 1.334 g of a solid acid catalyst and 137 g of 3-aminopropyltrihydroxysilane were added, the temperature was slowly raised to 140°C for reaction for 1 hour, 460 g of a polyetheramine having a structural formula as shown in Formula 2 was added through a constant pressure dropping funnel, after the addition was completed, the reaction was continued at 190°C for 3 hours, and the solvent dimethyl sulfoxide was finally removed by reduced pressure distillation to obtain a clay stabilizer S7.

[0036] The structural formula of polyetheramine is: Formula (4) The solid acid catalyst is composed of 10% graphite (600 mesh), 40% tin chloride and 50% bentonite in a mass fraction, and is prepared by soaking, drying and calcining at 500° C. in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:20.

[0037] Example 8 A four-necked flask equipped with a stirring paddle, a thermometer, a constant pressure dropping funnel and a water separator was placed in an oil bath, 100 g of dimethyl sulfoxide, 70 g of trimesic acid, 14.4 g of a solid acid catalyst and 200 g of 3-aminopropyltrimethoxysilane were added, the temperature was slowly raised to 140°C and the reaction was carried out for 2.5 h. 450 g of a polyetheramine having a structural formula as shown in Formula 3 was added through a constant pressure dropping funnel. After the addition was completed, the reaction was continued at 140°C for 3.5 h. Finally, the solvent dimethyl sulfoxide was removed by reduced pressure distillation to obtain a clay stabilizer S8.

[0038] Polyetheramine structure: Formula (5) The solid acid catalyst is composed of 10% graphite (400 mesh), 30% tin chloride and 60% bentonite in a mass fraction, and is prepared by soaking, drying and calcining at 600°C in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:15.

[0039] Example 9 A four-necked flask equipped with a stirring paddle, a thermometer, a constant pressure dropping funnel and a water separator was placed in an oil bath, 100 g of dimethyl sulfoxide, 84 g of trimesic acid, 3.7 g of a solid acid catalyst and 80 g of 3-aminopropyltrihydroxysilane were added, the temperature was slowly raised to 140°C and the reaction was carried out for 2 h. 206 g of diethylenetriamine was added through a constant pressure dropping funnel. After the addition was completed, the reaction was continued at 170°C for 2.5 h. Finally, the solvent dimethyl sulfoxide was removed by reduced pressure distillation to obtain clay stabilizer S9.

[0040] The solid acid catalyst is composed of 25% graphite (400 mesh), 30% tin chloride and 45% bentonite in a mass fraction, and is prepared by soaking in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:10, drying, and calcining at 550°C.

[0041] Example 10 A four-necked flask equipped with a stirring paddle, a thermometer, a constant pressure dropping funnel and a water separator was placed in an oil bath, 100 g of dimethylformamide, 84 g of trimesic acid, 8.76 g of a solid acid catalyst and 200 g of 3-aminopropyltriethoxysilane were added, the temperature was slowly raised to 140°C and the reaction was carried out for 1 hour. 300 g of tetraethylenepentamine was added through a constant pressure dropping funnel. After the addition was completed, the reaction was continued at 160°C for 2 hours. Finally, the solvent dimethyl sulfoxide was removed by reduced pressure distillation to obtain clay stabilizer S10.

[0042] The solid acid catalyst is composed of 15% graphite (500 mesh), 20% tin chloride and 65% bentonite in a mass fraction, and is prepared by soaking, drying and calcining at 500°C in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:20.

[0043] Embodiment 11 A four-necked flask equipped with a stirring paddle, a thermometer, a constant pressure dropping funnel and a water separator was placed in an oil bath, 100 g of dimethyl sulfoxide, 84 g of trimesic acid, 10.22 g of a solid acid catalyst and 120 g of 3-aminopropyltrimethoxysilane were added, the temperature was slowly raised to 130°C and the reaction was carried out for 2 h. 307 g of a polyetheramine having the structural formula 4 was added through a constant pressure dropping funnel. After the addition was completed, the reaction was continued at 150°C for 4 h. Finally, the solvent dimethyl sulfoxide was removed by vacuum distillation to obtain a clay stabilizer S11.

[0044] Polyetheramine structure Formula (6) The solid acid catalyst is composed of 15% graphite (400 mesh), 15% tin chloride and 70% bentonite in a mass fraction, and is prepared by soaking, drying and calcining at 500° C. in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:15.

[0045] Example 12 A four-necked flask equipped with a stirring paddle, a thermometer, a constant pressure dropping funnel and a water separator was placed in an oil bath, 100 g of dimethyl sulfoxide, 70 g of trimesic acid, 7.8 g of a solid acid catalyst and 120 g of 3-aminopropyltrimethoxysilane were added, the temperature was slowly raised to 140°C and the reaction was carried out for 3 h. 200 g of a polyetheramine having the structural formula 5 was added through a constant pressure dropping funnel. After the addition was completed, the reaction was continued at 170°C for 3 h. Finally, the solvent dimethyl sulfoxide was removed by vacuum distillation to obtain clay stabilizer S12.

[0046] Polyetheramine structure Formula (7) The solid acid catalyst is composed of 20% graphite (600 mesh), 40% tin chloride and 40% bentonite in a mass fraction, and is prepared by soaking, drying and calcining at 600°C in potassium permanganate and concentrated sulfuric acid in a mass ratio of 1:20.

[0047] Comparative Example 1 The method of Example 1 was followed, except that the solid acid catalyst was replaced with concentrated sulfuric acid. Other conditions were the same as those of Example 1. Clay stabilizer D1 was obtained.

[0048] Comparative Example 2 The method of Example 2 was followed, except that the reaction raw material diethylenetriamine was removed. Other conditions were the same as those of Example 2 to obtain a clay stabilizer D2.

[0049] Comparative Example 3 The method of Example 2 was followed, except that the reaction raw material 3-aminopropyltrimethoxysilane was removed. Other conditions were the same as those of Example 2. Clay stabilizer D3 was obtained.

[0050] Comparative Example 4 The method of Example 7 was followed, except that the reaction raw material polyetheramine D230 was removed. Other conditions were the same as those of Example 6 to obtain clay stabilizer D4.

[0051] Comparative Example 5 The method of Example 7 was followed, except that the reaction raw material 3-aminopropyltrihydroxysilane was removed. Other conditions were the same as those of Example 7. Clay stabilizer D5 was obtained.

[0052] Test Example 1 With reference to "SY / T5971-2016 Performance Evaluation Method of Clay Stabilizer for Water Injection", the anti-swelling rates of the clay stabilizers S1-S12, D1-D5 prepared in Examples 1-12 and Comparative Examples 1-5 and commercially available clay stabilizers at mass concentrations of 0.5%, 1.0% and 2% were tested.

[0053] With reference to "SY / T5971-2016 Performance Evaluation Method of Clay Stabilizer for Water Injection", the water wash resistance of the clay stabilizers S1-S12, D1-D5 prepared in Examples 1-12 and Comparative Examples 1-5 and commercially available clay stabilizers after three water washes at a mass concentration of 1% was tested.

[0054] The temperature resistance of clay stabilizers S1-S12, D1-D5 prepared in Examples 1-12 and Comparative Examples 1-5 and commercially available clay stabilizers was tested by high temperature aging test. The anti-swelling rate test steps after aging at 350°C are as follows: add 3.00g of sodium bentonite to 60mL of clay stabilizer solution with a mass concentration of 1%, shake well and mix, and then put it into an aging kettle; then put it into a high temperature aging furnace and age it at 350±2°C for 24h; after cooling to room temperature, transfer all the clay stabilizer solution in the aging kettle into a 100mL beaker, shake well, quickly take out 10mL and add it to a centrifuge tube, put it into a centrifuge with automatic balancing function, centrifuge it at 1500r / min for 15min, and read the expansion volume V1 of the bentonite. The high temperature anti-swelling rate calculation formula is shown in Formula 8.

[0055] (Formula 8) Where: F—high temperature anti-expansion rate, %; V0—volume of sodium bentonite in kerosene, mL; V1—volume of sodium bentonite in clay anti-swelling agent, mL; V2—volume of sodium bentonite in clean water, mL; The results of the anti-swelling properties, water washability and temperature resistance of the clay stabilizers S1-S12, D1-D5 prepared in Examples 1-12 and Comparative Examples 1-5 and commercially available clay stabilizers are shown in Table 1.

[0056] Table 1 Performance evaluation results

[0057] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0058] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A clay stabilizer, characterized in that: The clay stabilizer has a structure shown in formula (1) or formula (2); Wherein, n1=0 or 1, n2=any integer from 0 to 4, n3=any number from 1 to 5, R1 and R2 are the same or different and are independently H, CH3, or C2H5.

2. A method for preparing the clay stabilizer according to claim 1, characterized in that: It is prepared by amidation reaction with polyethyleneamine or polyetheramine, aminosilane and trimesic acid as raw materials, aprotic high-polar organic solvent as solvent and solid acid as catalyst.

3. The method for preparing a clay stabilizer according to claim 2, characterized in that: The conditions of the amidation reaction include: 均苯三酸 :n 多乙烯胺或聚醚胺 :n 胺基硅烷 =1:3:1.5~1:6:3, the amount of solid acid catalyst added is 0.5%-2% of the total mass of polyethyleneamine or polyetheramine, aminosilane and trimesic acid, the reaction temperature is 130-190℃, and the reaction time is 3-6h.

4. The method for preparing a clay stabilizer according to claim 2, characterized in that: The polyethyleneamine is at least one of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine.

5. The method for preparing a clay stabilizer according to claim 2, characterized in that: The aprotic high-polarity organic solvent is at least one of dimethyl sulfoxide and dimethylformamide.

6. The method for preparing a clay stabilizer according to claim 2, characterized in that: The trimesic acid is at least one of trimesic acid and trimesic acid.

7. The method for preparing a clay stabilizer according to claim 2, characterized in that: The aminosilane is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and 3-aminopropyltrihydroxysilane.

8. The method for preparing a clay stabilizer according to claim 2, characterized in that: The solid acid catalyst is prepared from graphite, tin chloride, bentonite, potassium permanganate and concentrated sulfuric acid.

9. The method for preparing a clay stabilizer according to claim 8, characterized in that: The solid acid catalyst is composed of 10-30% graphite (400-600 mesh), 20-45% tin chloride and 25-70% bentonite by mass fraction, and is prepared by soaking in potassium permanganate and concentrated sulfuric acid at a mass ratio of 1:10-20, drying, and calcining at 500-600°C.

10. An application of the clay stabilizer according to claim 1, characterized in that: The clay stabilizer is used in the field of oil field production.

Citation Information

Patent Citations

  • Wetting reversal inhibitor for drilling fluid and preparation method of wetting reversal inhibitor

    CN112920783A

  • High-temperature-resistant efficient clay stabilizer

    CN113088265A

  • Method for modifying the surface properties of the smectic clays

    PL397236A1

  • KR20190071895A